La revolución de las locas: de la crítica social a la constitución poética en el Manifiesto, de Pedro Lemebel (Crítica) - Galván Díaz, Félix Joaquín (2023)
In September 1986, Manifiesto, a poem by Pedro Lemebel, was presented during a Communist Party event at Estación Mapocho in Santiago. Critics claim that the text questioned the neoliberal values that marginalized dissident sexualities and their prolongation in the political left. However, in this article, through textual analysis and considering the context of production, I propose, on the one hand, that it challenged the Marxist precepts on homosexuality to avoid the segregation of sexual dissidents in case of achieving the communist revolution in Chile —as it happened in Cuba—; on the other hand, that the ethical-political attitude of the composition reveals a poetic that imbricates body, gender, sexuality, and social commitment.